Reply to Three Commentaries on "Hypnosis Reconsidered, Resituated, and Redefined" - Crabtree, Adam (Journal of Scientific Exploration, 2012)
In responding to the comments (pp. 327–359) on my article (pp. 295–325) in this issue of the JSE, I will take up the issues raised by each of the three Commentaries separately. I take this approach because their concerns seem to be quite different, and by treating them individually I can best do justice to each.